The Future Direction of the Adult Heart Allocation System in the United States. Issue 1 (January 2015) - Meyer, D. M.; Rogers, J. G.; Edwards, L. B.; Callahan, E. R.; Webber, S. A.; Johnson, M. R.; Vega, J. D.; Zucker, M. J.; Cleveland, J. C.
<x xml:space="preserve">Abstract</x> Ensuring equitable and fair organ allocation is a central charge of the United Network for Organ Sharing (UNOS) as the Organ Procurement and Transplantation Network (OPTN) through its contract with the Department of Health and Human Services (DHHS). The OPTN/UNOS Board initiated a reassessment of the current allocation system. This paper describes the efforts of the OPTN/UNOS Heart Subcommittee, acting on behalf of the OPTN/UNOS Thoracic Organ Transplantation Committee, to modify the current allocation system. The Subcommittee assessed the limitations of the current three‐tiered system, outcomes of patients with status exceptions, emerging ventricular assist device (VAD) population, options for improved geographic sharing and status of potentially disenfranchised groups. They analyzed waiting list and posttransplant mortality rates of a contemporary cohort of patient groups at risk, in collaboration with the Scientific Registry of Transplant Recipients to develop a proposed multi‐tiered allocation scheme. This proposal provides a framework for simulation modeling to project whether candidates would have better waitlist survival in the revised allocation system, and whether posttransplant survival would remain stable. The tiers are subject to change, based on further analysis by the Heart Subcommittee and will lead to the development of a more effective and equitable heart allocation system.